IMPROVING THE ABILITY OF MOTOR OILS TO THE EFFECTS OF HIGH TEMPERATURES (Academia Science Repository, 2023)
In the high temperature zone, the oil burns completely or carbonaceous particles remain, which cannot remain on the surface devoid of a binding medium. The greatest danger of varnish deposition is for piston rings. By filling the gaps formed by the piston rings and the grooves drilled in the pistons, it reduces the mobility of the rings. To reduce or prevent the formation of carbon deposits, special surfactants called detergent-dispersing additives are introduced into engine oils. The effect of such additives is based on their ability to loosen, wash off deposits from the surface of parts and transfer insoluble substances into suspension and keep these particles in this state without enlargement.